2001
DOI: 10.4049/jimmunol.167.4.2030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Tolerance of CD4+ T Cells In Vivo: Multiple Thresholds in Response to a Constant Level of Antigen Presentation

Abstract: The in vivo T cell response to persistent Ag contains a hyporesponsive phase following an initial expansion and subsequent partial deletion of the responding cells. The mechanism(s) responsible for this tolerance process is poorly understood. In this study, we describe a new paired transgenic model (TCR and Ag), which within 7–14 days produces 20–40 million hyporesponsive T cells. This state is characterized by an 85–95% reduction in all cytokine production, an impairment of re-expression of CD25 and CD69, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
107
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 45 publications
11
107
0
Order By: Relevance
“…S2). Thus, T cells that had expanded under persistent antigenic stimulation in lymphopenic hosts appeared to have developed a state of functional unresponsiveness similar to that previously described as T cell adaptation (3,4). Whereas unresponsive T cells did not produce IL-2, they secreted IFN-␥ in response to anti-CD3 stimulation (see supplemental Fig.…”
Section: H-y-specific Cd4 ϩ T Cells Develop a State Of Functional Unrsupporting
confidence: 64%
See 4 more Smart Citations
“…S2). Thus, T cells that had expanded under persistent antigenic stimulation in lymphopenic hosts appeared to have developed a state of functional unresponsiveness similar to that previously described as T cell adaptation (3,4). Whereas unresponsive T cells did not produce IL-2, they secreted IFN-␥ in response to anti-CD3 stimulation (see supplemental Fig.…”
Section: H-y-specific Cd4 ϩ T Cells Develop a State Of Functional Unrsupporting
confidence: 64%
“…In fact, it has been shown that adapted T cells are characterized by their ability to calibrate their responsiveness to a persistent Ag (2)(3)(4). In this study, we show for the first time that negative costimulation was critical for CD4 ϩ T cells to maintain their adaptation to systemic mHA and that negative costimulation blockade by Ab treatment converted adapted T cells into aggressive effector cells.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations